FAKTOR – FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA INDUSTRI MANUFAKTUR BESAR DAN MENENGAH PADA TINGKAT KABUPATEN / KOTA DI JAWA TIMUR - Kholidah Azhar; Zainal Arifin (Jurnal Ekonomi Pembangunan, 2011)
This research tries to know factor that regard industrial labour absorption manufacturing outgrows and intermediate on regency / city at Javanese East. With insert free variable total industrial pay, industrial raw material, total manufacturing industrial enterprise and manufacturing industry production is gotten usufructs that variable fourth that free signifikan's ala having for to labouring absorption on industrial manufacturing with determinant coefficient R2  as big as 94,8% on zoom glosses over 5%.